Association of KCNJ2 Genetic Variants with Susceptibility to Thyrotoxic Periodic Paralysis in Patients with Graves’ Disease - Park, Suyeon; Kim, Tae Yong; Sim, Soyoung; Oh, Hye-Seon; Song, Eyun; Kim, Mijin; Kwon, Hyemi; Choi, Yun Mi; Jeon, Min Ji; Kim, Won Gu; Shong, Young Kee; Kim, Won Bae (Experimental and Clinical Endocrinology & Diabetes, 2017)
Objective: Thyrotoxic periodic paralysis (TPP) is characterized by acute onset paralysis and hypokalemia predominantly in male patients with thyrotoxicosis. Recent studies have emphasized the importance of potassium channels, which might explain the underlying mechanism of TPP. The KCNJ2 gene encodes the inward-rectifying potassium channel. In this study, we evaluated the role of KCNJ2 in the development of TPP.Design: Case-control analysis of KCNJ2 genetic association with TPP.Patients: 83 male patients with Graves’ disease (GD) were recruited for this study; 43 patients had TPP, whereas 40 patients had no history of TPP.Measurements: We analyzed the genotype and allelic frequency of a single-nucleotide polymorphism (SNP; rs312691) (C>T) adjacent to the KCNJ2 gene that is known to be related to TPP development.Results: The frequency of the CC genotype of the rs312691 SNP was 0.51 in TPP patients and 0.05 in controls (p-value=6.18×10−6). The C allele frequency of the SNP was 0.67 in the TPP group and 0.38 in the control group (odds ratio 3.24; 95% confidence interval 1.65–6.51; p-value, 3.1×10−4). The rs312691 SNP was significantly associated with TPP.Conclusions: We demonstrated that the rs312691 SNP was significantly associated with TPP. These findings suggest that KCNJ2 plays an important role in the pathophysiology of TPP in Korean GD patients with TPP.